The Advantages, Risks, and Rules of Installing Video Surveillance in Workplaces - Paneva, Ana (Central European Academy Law Review, 2025)
The monitoring of employees is an issue closely related to the right to privacy, protection of personal data, and dignity. The development of modern technology has brought many benefits, but also risks – to which special attention should be paid, especially with the installation of video surveillance systems. The data collected during video surveillance is usually images relating to an identified person, or a person who can be identified – directly or indirectly – to monitor behaviour. As video monitoring spreads, people’s freedom of movement and behaviour, and their privacy, are therefore reduced. Video surveillance is used for various purposes, but mostly for security - where guarantees must be taken to avoid any misuse for completely different and individual purposes (e.g. for marketing; to monitor the work of employees, etc.). This paper provides an analysis of the rules and regulations in Macedonian legislation. Special attention is paid to the procedure and circumstances under which it is possible to install permanent video surveillance to control work activity.